Combination of noninvasive brain stimulation and constraint-induced movement therapy in patients with stroke: a systematic review and meta-analysis. (1st February 2023) - Abdullahi, Auwal; Wong, Thomson WL; Van Criekinge, Tamaya; Ng, Shamay SM
ABSTRACT: Introduction: Constraint-induced movement therapy (CIMT) and noninvasive brain stimulation (NIBS) are used to counteract learned nonuse phenomenon and imbalance in interhemispheric inhibition following stroke. The aim of this study is to summarize the available evidence on the effects of combining NIBS with CIMT in patients with stroke. Method: PubMed, Embase, Web of Science (WoS), PEDro, OTSeeker, and CENTRAL were searched for randomized controlled trials comparing the use of NIBS+CIMT with sham NIBS+CIMT. Data on variables such as time since stroke and mean scores and standard deviations on outcomes assessed such as motor function were extracted. Cochrane risks of bias assessment tool and PEDro scale were used to assess the risk of bias and methodological quality of the included studies. Results: The results showed that both NIBS+CIMT and sham NIBS+CIMT improved all outcomes post-intervention and at follow-up. However, NIBS+CIMT is superior to sham NIBS+CIMT at improving level of motor impairment (SMD = 1.75, 95% CI = 0.49 to 3.01, P = 0.007) post-intervention and hand function (SMD = 1.21, 95% CI = 0.07 to 2.35, P = 0.04) at follow-up. Conclusions: The addition of NIBS to CIMT seems to provide additional benefits to the recovery of function following stroke.